PENGARUH LAYANAN BIMBINGAN DAN KONSELING TERHADAP PERUBAHAN TINGKAH LAKU SISWA KELAS IX SMP ISLAM INTEGRAL LUQMAN AL HAKIM BATAM - Afrizawati; M. Sidik; Safarina (JURNAL AS-SAID, 2021)
Counseling guidance is the process of providing assistance by an expert to a person or several individuals, whether children, adolescents, or adults, so that the person being guided can develop their own and independent abilities by utilizing individual strengths and existing facilities. and can be developed based on applicable norms. With the guidance and counseling is expected to provide solutions for students in schools so that students become better and have a healthy mentality. This study aims to determine the effect of guidance and counseling on behavioral changes in class IX students of SMP Islam Integral Luqman Al Hakim Batam. The method in this study uses the explanatory method, the product moment correlation research technique with a quantitative approach, namely the first variable, the influence of guidance and counseling services and the second variable. The results of this study indicate that there is a relationship between guidance and counseling services and changes in the behavior of class IX students of Luqman Al Hakim Islamic Junior High School Batam.